Isolationand Identification of mouse bone marrow derived mesenchymal stem cells - AL-Qaisy, Baydaa A. (Iraqi Journal of Cancer and Medical Genetics, 2014)
Bone marrow derived mesenchymal stem cells (BM-MSCs) were successfully used in regenerative medicine. The purpose of this study was to isolate and characterize mesenchymal stem cells from mouse bone marrow for their subsequent use in researches. Previous data suggest that BM-MSCs are typically enriched by plastic adherent cultures, fibroplastoid cell fraction. However, Identification of MSCs achieved through their morphology, phenotypic characteristics and their biological behavior. The cellular morphology played a major part in identifying MSCs in vitro. In general, immature MSCs appeared as small, spindle-shaped cells, whereas mature MSCs was displayed as larger cells with a flat, polygonal morphology. Cells also tended to be locally confluent, growing in distinct colonies. Immunophenotypic analysis demonstrated that mouse BM-MSCs at passage three uniformly positive for CD44, CD90, CD105 and CD106. However, MSCs were always found to be negative for heamatopoietic specific markers CD34, CD45, and endothelial marker CD31. By concluding, mesenchymal stem cells can be successfully derived from mouse bone marrow by direct plating method. These cells represent a valuable source of stem cells for restoring the damaged organs